PENINGKATAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS 2 SD MELALUI PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) - Rahmawati, Lusiana Dwi; Agustini, Ferina; Saputro, Susilo Adi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The issue of student’s learning outcomes is crucial to address by providing solution to brige learning gaps, such as tailoring teaching to individual levels of understanding. To address edicational challenges related to low learning outcomes, the outhor intends to implement the Teaching at the Right Level (TaRL) approach to improve student’s performance in Mathematics. The research subjects consisted of 27 second-grade students. This study employed a mixed-methods approach, combining quantitative and qualitative methods. The quantitative method was used to collect numerical data through surveys or questionnaires. Data collection included results from pretest and posttest conducted before and after the teacher implemented the TaRL approach in Mathematics lessons for second-grade students at SD N Pandeanlamper 03 Semarang. Overall, the study findings indicate that the implementation of the TaRL approach in Mathematics successfully enhanced the quality of learning. The TaRL approach proves to be a highly effective alternative solution for improving students’ learning outcomes, especially in understanding Mathematics, a subject often perceived as difficult by most student. Based on the results of this research, it can be concluded that the Teaching at the Right Level (TaRL) approach effectively improves the Mathematics learning outcomes of second-grade students at SD N Pandeanlamper 03 Semarang. These findings suggest that TaRL could serve as a highly effective alternative for enhancing the quality of Mathematics education in primary school.